Strategi Pembelajaran Berbasis Masalah pada Kelas Virtual: Implementasi dan Dampak - Aqilatun Ni'mah; Faisol abrori; Yunus Nur Hidayat; Attiin Machfiroh; Imroatus Sulthoniyah (Universitas Insan Budi Utomo, 2024)
This study aims to analyze the implementation of Problem-Based Learning (PBL) strategies in virtual classrooms and their impact on student engagement and learning outcomes. PBL is an approach that emphasizes solving real-world problems as part of the learning process. However, its application in online environments faces various challenges, such as limited interaction, varying student motivation, and technological readiness. This study employs a literature review method by analyzing previous research related to the implementation of PBL in virtual classrooms. The findings indicate that PBL in online learning can be effective if supported by appropriate strategies, such as the use of collaborative technology, active facilitation by educators, and the integration of gamification elements to enhance student engagement. Additionally, technological infrastructure readiness and digital literacy play crucial roles in the successful implementation of PBL in virtual settings. Therefore, this study recommends the development of educational policies that are more adaptive to the needs of problem-based learning in digital environments and training programs for educators to optimize PBL implementation in online learning.